Potential distribution of Aspidoscelis gularis (squamata: teiidae) complex in Mexico - Pérez-Almazán, Carlos (Universidad Autónoma de Tamaulipas, 2014)
The distribution of Aspidoscelis gularis complex in Mexico has been difficult to model due to taxonomic problems facing its members; and because, published models exclude typical areas where taxa have been reported. The goal of this study was to update the information on the distribution of A. gularis complex and suggest issues for modeling species groups considered “complex”, as well as any taxonomic level. The generated information allowed developing a distribution model through Mahalanobis-typicality algorithm in IDRISI Taiga and validated using the area under the curve (AUC), which obtained a value of 0.932. The modeled distribution spanned states belonging to the Mexican Plateau. It was found that the taxa of complex were associated with the Mexican Plateau´s vegetation classified and named as Chihuahuan desert, which is composed mainly by xeric scrub and grasslands, suggesting a factor limiting their distribution in northern and central Mexico, similar to other groups of reptiles.